Marine Policy in Holding and Handling Marine Natural Asset as An Attempt to Recognize Indonesia as The Sector’s Maritime Axis - Hario Istiqlal Agung; Hikmat Zakky Almubaroq (Faculty of Social Science, Universitas Negeri Padang, 2022)
The maritime axis is now increasingly popular and attracts the attention of many parties, including the mass media which also often brings up the term in the news in recent times. The emergence of the term cannot be separated from the idea of ​​President Joko Widodo who wants to make Indonesia as the world's maritime axis, also wants to make Indonesian waters a territory safe waters in the world for all marine activities, and for that, the government will ensure security and safety of sea transportation carried out by the community and business actors. The development of maritime affairs cannot be done all at once. To optimize maritime development at the national level, regional and global, and especially in achieving the world maritime axis requires direction, orientation, strategy, and anticipation of effective, consistent, and sustainable development. Therefore, the researcher saw the implementation of the maritime axis from a policy perspective. Issues that will be the focus of this research are firstly how the development of the world maritime axis concept in Indonesia, secondly how to implement Indonesia's maritime axis from a policy perspective. The purpose of this research is to know the development of the concept of the world maritime axis in Indonesia and its implementation. Based on the results of research that Indonesia has implemented the concept of the world maritime axis by issuing policies and their implementation; it is recommended that Indonesia has a pivot law maritime world to answer challenges to realize Indonesia's excellence. The uses of this research order to information and development of law and practice as input for stakeholders including the Government, experts, academics, practitioners and the public.